Utilization of mental health care services among older adults with depression in Canada - Crabb, Rebecca (University of Ottawa (Canada), 2008)
Previous studies have indicated a tendency for older adults to under-utilize available services and medications for depression. Three studies were undertaken to provide representative Canadian data on rates of mental health service use by older Canadian adults with depression, in three domains: (1) mental health consultations with health care professionals, (2) utilization of psychoactive medications commonly used in treatment of late-life depression, and (3) mental health-related utilization of alternative or complementary services and products. An additional objective was to examine the relative effect of age on service utilization after accounting for other potentially relevant sociodemographic and clinical characteristics. Data for the studies was obtained from Statistics Canada's Canadian Community Health Survey, Cycles 1.1 (Study 1) and 1.2 (Studies 2 and 3). Older adults were less likely than middle-aged adults to seek mental health care services from any health care professionals, and especially from specialty mental health professionals (psychologists or psychiatrists). Compared to middle-aged adults, older adults used antidepressant medications at a lower rate and benzodiazepines at a higher rate. Age-related patterns in mental health-related use of CAM did not directly correspond to age-related patterns in conventional mental health care utilization. The results of the three dissertation studies clearly indicate that mental health utilization patterns continue to differ significantly among middle-aged, younger- and older-older adults with depression. These findings have significant implications in terms of initiatives to improve the recognition and treatment of late-life depression.
Keywords: Health Sciences, Mental Health.; Gerontology.; Psychology, Clinical.